The Effect of Intrapartum Oxygen Supplementation on Category II Fetal Monitoring. Issue 5 (May 2021) - Raghuraman, Nandini; López, Julia D.; Carter, Ebony B.; Stout, Molly J.; Macones, George A.; Tuuli, Methodius G.; Cahill, Alison G.
Abstract : (Abstracted from Am J Obstet Gynecol 2020;223:905.e1–905.e7) The administration of maternal oxygenation (O2 ) is a commonly used resuscitation technique for fetuses with category II electronic fetal monitoring (EFM) patterns. In cases of recurrent fetal decelerations, the goal of maternal O2 supplementation is to increase fetal oxygenation.